2011
DOI: 10.1016/j.yjmcc.2010.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The p38 mitogen-activated protein kinase pathway—A potential target for intervention in infarction, hypertrophy, and heart failure

Abstract: The p38 mitogen-activated protein kinases (p38s) are stress activated ser/thr kinases. Their activation has been associated with various pathological stressors in the heart. Activated p38 is implicated in a wide spectrum of cardiac pathologies, including hypertrophy, myocardial infarction, as well as systolic and diastolic heart failure. In this review, the specific contribution of different isoforms of p38 kinases to cardiac diseases as well as TAB-1 mediated non-canonical activation pathway are discussed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 83 publications
2
121
1
7
Order By: Relevance
“…32,33 Inhibiting p38 and JNK1/2 signaling with an appropriate pharmacological agent could delay the transition toward heart failure. 20,34 These results suggest that the heart-protective role of USP18 is likely attributed to its interference with p38 and JNK1/2 signaling.…”
Section: Discussionmentioning
confidence: 85%
“…32,33 Inhibiting p38 and JNK1/2 signaling with an appropriate pharmacological agent could delay the transition toward heart failure. 20,34 These results suggest that the heart-protective role of USP18 is likely attributed to its interference with p38 and JNK1/2 signaling.…”
Section: Discussionmentioning
confidence: 85%
“…Given that mitogen-activated protein kinase signaling pathways, including ERK1/2, p38, and JNK1/2, have been shown to play important roles in cardiac hypertrophy, [24][25][26] Western blots were performed to analyze whether TRIM8 regulates mitogen-activated protein kinase signaling pathways. Our study demonstrated that the exaggerated hypertrophic response in TRIM8-transgenic hearts was accompanied by enhanced activation of P38 and JNK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are well-accepted critical players in the development of pathological cardiac hypertrophy and HF. [24][25][26] In response to pressure overload, neither the absence nor the overexpression of TRIM8 in mouse hearts altered the activity of MEK1/2 and ERK1/2. Conversely, the AB-induced activation of P38 and JNK1/2 was significantly attenuated in TRIM8-knockout hearts but enhanced in TRIM8-transgenic hearts ( Figure 5A and 5B).…”
Section: Trim8 Enhances Hypertrophic Stresses-induced Activation Of Pmentioning
confidence: 99%
“…All of these pathways have also been shown to be activated in the myocardium early after experimental MI; see recent comprehensive reviews on NF-κB (Gordon et al, 2011), p38 (Marber et al, 2011;Turner, 2011), JNK (Turner, 2011), ERK and Akt; the latter being components of the reperfusion injury salvage kinase (RISK) pathway that is considered cardioprotective (Hausenloy et al, 2005). However, these studies do not shed particular light on IL-1 signalling in CF due to the heterogeneity of cell types in the 16 heart and the multitude of potential stimuli for these pathways after MI (in addition to IL-1).…”
Section: Il-1 Signalling In Cfmentioning
confidence: 99%
“…The p38 MAPK pathway plays an important role in regulating various aspects of the myocardial remodelling process, including CF function (Marber et al, 2011;Turner, 2011).…”
Section: Il-1 Signalling In Cfmentioning
confidence: 99%